1954
DOI: 10.1172/jci102959
|View full text |Cite
|
Sign up to set email alerts
|

Bone as a Sodium and Potassium Reservoir 12

Abstract: Gamble, Ross, and Tisdall (1) originally pointed out that electrolytes and water were lost from the body during fasting in a manner which could be reasonably predicted from the concentration of salts in the body fluids. This concept is the basis for the study of changes in body composition by examination of electrolyte balance and weight changes. Darrow, Da Silva, and Stevenson (2) elaborated the method of calculation and showed that shifts of sodium between extracellular and intracellular fluid could be inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
1

Year Published

1954
1954
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(83 citation statements)
references
References 12 publications
7
75
0
1
Order By: Relevance
“…In two of the preshydrogen buffering might occur. This probably includes not only muscle and other soft tissues, but also bone, which has been demonstrated to have a large labile store of sodium and potassium (11). ent cases and in Folling's experiment, the estimated loss of intracellular potassium was considerably less than the calculated uptake of hydrogen (Table III), indicating that some other cellular cation, probably sodium, was also exchanged.…”
Section: B Post-acidification Periodmentioning
confidence: 81%
“…In two of the preshydrogen buffering might occur. This probably includes not only muscle and other soft tissues, but also bone, which has been demonstrated to have a large labile store of sodium and potassium (11). ent cases and in Folling's experiment, the estimated loss of intracellular potassium was considerably less than the calculated uptake of hydrogen (Table III), indicating that some other cellular cation, probably sodium, was also exchanged.…”
Section: B Post-acidification Periodmentioning
confidence: 81%
“…The corrected exchangeable sodium is only reduced by some 10 per cent on the assumption that all of Until recently, direct evidence of displacement of sodium from bone to circulating extracellular fluid has been lacking. Bergstrom (40) observed that in rats acute sodium and potassium depletion resulted in a mobilization of both of these cations from bone. Other investigators (25) could not demonstrate any significant changes in bone sodium content in adrenalectomized dogs although the rate of bone sodium exchange using Na24 as a tracer appeared to be depressed in the adrenal insufficient animals as compared to the controls.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of reported animal studies, however, it can be predicted that the extracellular fluid compartment would show the greatest changes followed by the exchangeable fraction of bone sodium (32)(33)(34)(35)(36)(37) 2. Body sodium exchanging after the first 24 to 48 hours was not a significant fraction of the metabolically active sodium pool, nor did it interfere with long-term measurements of this pool by isotope dilution methods.…”
Section: Discussionmentioning
confidence: 99%